An Approach for Fish Detection in Underwater Images - Martinho, Laura A.; Neto, Odalisio L. S.; Calvalcanti, João M. B.; Pio, José L. S.; Oliveira, Felipe G. (Anais do Workshop de Visão Computacional (WVC), 2023)
Underwater images are widely used for understanding subaquatic environments. However, underwater images are severely degraded by light absorption and scattering, as it propagates in water during image acquisition causing color distortion, low contrast and noise. These problems can interfere in underwater vision tasks, such as recognition and detection. In this paper we propose an approach for fish detection in underwater environments. In order to achieve this goal, the proposed method is composed by two main steps: i) Image Restoration, processing the underwater images to enhance the image quality; and ii) Fish Detection, to identify the presence of fish in underwater images. Additionally, in this paper we introduce an underwater image dataset with the presence of fish. Through the experimental process using the proposed dataset, the obtained results demonstrate the precision and robustness of the proposed approach, achieving accuracy of 98.04% in the fish detection task.